2016
DOI: 10.1139/cjm-2015-0647
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the efficacy of co-inoculation of wheat seedlings with the associative bacteriaPaenibacillus polymyxa1465 andAzospirillum brasilenseSp245

Abstract: Co-inoculation of associative bacteria, which have high nitrogen-fixing activity, tolerance for environmental conditions, and the ability to compete with the natural microflora, is used widely to enhance the growth and yields of agricultural plants. We evaluated the ability of 2 co-inoculated plant-growth-promoting rhizobacteria, Paenibacillus polymyxa 1465 and Azospirillum brasilense Sp245, to colonize roots of wheat (Triticum aestivum L. 'Saratovskaya 29') seedlings, and we assessed the morphometric paramete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…EPS are combinations of monomers and polymers consisting of sugar compounds connected via glyosidic linkages 14,24,25 . EPS length, composition and formation vary considerably 2628 . The main factors that influence EPS interactions include the charges, polymer functional groups, backbone and chain fitness, and the relative concentrations of the constituents 14,24,25 .…”
Section: Discussionmentioning
confidence: 99%
“…EPS are combinations of monomers and polymers consisting of sugar compounds connected via glyosidic linkages 14,24,25 . EPS length, composition and formation vary considerably 2628 . The main factors that influence EPS interactions include the charges, polymer functional groups, backbone and chain fitness, and the relative concentrations of the constituents 14,24,25 .…”
Section: Discussionmentioning
confidence: 99%
“…Species integrations are essentially the ratios of microbial species in co-inoculants. The ratios of microbial species in co-inoculants were mostly 1:1 ( Maheshwari et al, 2010 ; Yegorenkova et al, 2016 ). In this study, we set two ratios according to soil fertility, microbial activity and cucumber nutrient requirement.…”
Section: Discussionmentioning
confidence: 99%
“…Species integrations were essentially the ratios of microbial species in co-inoculants. The ratios of microbial species in co-inoculants were mostly 1:1 ( Maheshwari et al, 2010 ; Yegorenkova et al, 2016 ). Saleem et al (2016) revealed that species richness had positive effects on efficiency and stabilize of microbial co-inoculants and different ratios of a specie had different effects on co-inoculants efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…Many in-depth studies have been conducted to improve knowledge on the bacteria-plant association, employing techniques involving genomics, proteomics, and metabolomics (Mukherjee et al 2016;Spaepen and Vanderleyden 2015) as well as co-inoculation (Yegorenkova et al 2016) and the industrial production of inoculants (Bashan and Bashan 2015). However, there is still a lack of information regarding the magnitude and exact mechanisms involved in the positive effects of bacterial inoculants on N nutrition in plants under field conditions, including the role played by PGPB in the recovery of N derived from fertilizer.…”
Section: Introductionmentioning
confidence: 99%